Creating a valid and reliable perception of airport sustainability scale. (2015) - Cremer, Ismael; Rice, Stephen; Michaels, Alexander; Oyman, Korhan
A perception of airport sustainability scale (PASS) was created for the purpose of measuring consumer perceptions about the sustainability aspects of an airport. A total of 617 participants were solicited to help generate items for the scale, narrow down the list of items to the most relevant items related to airport sustainability, and test the final scale for validity and reliability. A factor analysis using the principal components and varimax rotation loaded strongly on one factor, providing evidence for validity. Reliability was tested via Cronbach's alpha and Guttmann's split-half tests, indicating high consistency and reliability. The scale was then tested to examine the correlation between the airport's PASS score given by the passengers with respect to their willingness to fiscally support the airport in sustainable practices through passenger fees.